The Effect of Financial Literacy on Investment Decisions Mediated by Financial Behavior - Marpaung, Ivan Andeska; Setyaningrum, Retno Purwani; Dasman, Sunita (Lentera Ilmu Nusantara, 2024)
The expected benefits of this study are to deepen the results of previous research on how financial literacy variables affect investment decision variables and also to analyze whether financial behavior variables as mediating variables can strengthen or weaken the relationship between financial literacy variables and investment decision variables. The sample population used was 34 employees who worked in the South Jakarta Jamsostek Tower area. The research data was obtained by distributing questionnaires using a Likert scale as a measuring tool. The technique used to understand the data is descriptive quantitative and assisted by data analysis of the Smart PLS application. The results showed that financial literacy variables have an influence on investment decision variables and financial literacy variables have an influence on financial behavior variables. However, financial behavior does not affect the investment decision variable and the financial behavior variable does not provide influence in mediating the effect of financial literacy on investment decisions.